Teachers’ Perception, Plan, Implementation, and Evaluation toward The Use of Super Minds Textbook in EFL Classroom - Septiana, Eka; Mujiyanto, Januarius; Sutopo, Djoko (Universitas Negeri Semarang, 2020)
This study proposes to explore teachers’ perception, plan, implementation, and evaluation toward the use of Super Minds textbook in EFL Classroom. The study employed case study approach. Two teachers were selected to become participants in this study. The data were gathered through questionnaire, semi-structured interview, classroom observations, and document analysis. The result of this study revealed that both teachers had positive perception on the use of Super Minds textbook. That was indicated from their positive thoughts on their planning and implementation that Super Minds textbook became an effective and engaging learning source in the classroom. The two teachers planned the lesson using the topic and material from Super Minds textbook. Although the teachers’ did the same stages in planning, the plan was implemented and resulted in different ways. They used supplementary materials provided from the textbook package as their teaching aids for enhancing the students in the classroom. The two teachers are evaluated as good practitioners for students in using Super Minds textbook. All this result leads to the alignment between teachers’ perception, plans, implementation, and evaluation. It was proven by teachers’ positive perception on toward the use of Super Minds textbook reflected in their planning, actual implementation, and evaluation in the classroom. It was expected for further research to possibly continue this study by using another textbook in different level of students so that it will give another perspective.